Computational-Thinking Based Learning Activities for Physics in Indonesian New Curriculum Through a Student Worksheet Development - Rahmawati, Siti Nur; Fauzi, Ahmad; Supurwoko, Supurwoko (STKIP Singkawang, 2024)
This research aims to investigate the practicality of the CT-based learning integrated in the physics high school subject through a development of student worksheet. The CT-based learning adapted from Palts and Pedaste’s problem-solving cycle for CT and involved Weintrop’s taxonomy of CT activities in math and science as the reference activities. The study used Plomp’s model, started from the preliminary research, followed by the development phase and evaluation that contained the validity content and practicality evaluation. The content showed high validity scores thus it was continued with the practicality evaluation by carrying out a micro-evaluation to the target users that involved observation, interview, and questionnaire addressing. The evaluation showed that the learning activities through the student worksheet had high practicality scores thus it is possible to be used and adapted to other subject matters.